Digital Marketing Support and Business Development Using Online Marketing Tools: An Experimental Analysis - Warokka, Ari; Sjahruddin, Herman; Sriyanto, Sriyanto; Noerhartati, Endang; Saddhono, Kundharu (International Journal of Psychosocial Rehabilitation, 2020)
The amount of research related to internet commerce has massive rapidly since the dawn of the net Age. We have a tendency to tend to in addition illustrious several subject areas that need any exploration. The compilation of the methodologies used, and internet commerce topics being studied can serve to encourage analyzers to strengthen current analysis and explore new areas of this analysis. A review of the literature base will facilitate verify the topics that square measure explored additionally as verify topics for any analysis. we have a tendency to tend to analyzed printed over the past eighteen years and gift in thirty high info Systems journals and twenty 2 articles at intervals the high 5 commerce journals. This analysis collects, synthesizes, and analyses every the analysis strategies and content is topics, focus, classes of this literature, then discusses associate in nursing agenda for future analysis efforts. The results indicate associate in nursing increasing level of activity throughout the 18- year quantity a biased distribution of internet commerce articles focused on preliminary methodologies, different and several other analysis strategies that were either underrepresented or absent from the pool of internet research.